Technological Trends Involving Probiotics in the Treatment of Diabetic Neuropathy: A Patent Review (2009-2022) - Silva Santos, Sthefane; de Souza, Mariana B.; Sales Lauria, Pedro Santana; Lima Juiz, Paulo José; Flora Villarreal, Cristiane; Maurício Viana, Max Denisson (Current Diabetes Reviews, 2024)
Background: Diabetic neuropathy (DN) causes neuropathic pain, and current treatments are unsatisfactory. Recently studies have demonstrated an assertive correlation between gut microbiota and pain modulation. Objective: Considering the emerging search for new therapies for the control of DN and the growing commercial interest in the probiotics market, this study aimed to provide patents on the use of probiotics in the control of DN. Methods: This is a patent prospection performed in the Espacenet Patent database, using the association of keywords and IPC related to probiotics in medical preparations and foods, from 2009 to December 2022. Results: Results have shown that in 2020, there was a boom in patent filing in the area. Asian countries accounted for more than 50% of all 48 inventions (n = 48), with Japan as the only applicant in 2021. Products being developed in recent years point to effects that may represent an advancement in DN treatment, such as reduced concentration of pro-inflammatory mediators, metabolites and neurotransmitters release, and hypoglycemic potential. All effects were more related to the Lactobacillus and Bifidobacterium genera, associated with more than one property mentioned. Conclusion: The mechanisms attributed to the microorganisms suggest the therapeutic potential of probiotics in the non-pharmacological treatment of pain. New applications for probiotics have resulted from great research interest by academia, but also reflect commercial interests despite the paucity of clinical trials. Thus, the present work supports the evolution of research to explore the benefits of probiotics and their clinical use in DN.
Keywords: reactive oxygen species